RESPONS PERTUMBUHAN DAN HASIL PADI GOGO PADA BERBAGAI KONSENTRASI ISOLAT BAKTERI EPIFIT - Aris Aksarah; J Jumardin; Ruth Tibian (Fapetrik-UMPAR, 2019)
This study aims to study the growth response and yield of upland rice at various concentrations of epiphytic bacterial isolates. The study was arranged using a randomized block design (RCBD), with treatment concentrations of epiphytic bacterial isolates, which consisted of four concentrations. Namely without epiphytic isolates (control), epiphytic bacterial isolates 45 ml/l of water, epiphytic bacterial isolates 50 ml/l of water, and epiphytic bacterial isolates of 55 ml/l of water. The results showed that the treatment of various concentrations of epiphytic bacterial isolates significantly affected the growth and yield of upland rice. Treatment concentration of 55 ml/l of water gives the best effect which is higher than other treatments on plant height, number of leaves, number of tillers, number of productive tillers, panicle length, number of grains, wet and dry weight and yield of upland rice.